Information and Analysis System Stages of Family Welfare in District Balong - Ayu, Eka Arynda; Widaningrum, Ida (Scientific Journal of Informatics, 2017)
Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) is a family that formed due to legal marriage, is able to meet the needs of the spiritual and the material that is decent, devoted to God Almighty, have a relationship that is harmonious and balanced between members and between families with the community and the environment. Every year the government to collect data on the status of a prosperous family stage where the purpose of the data collection is in the framework of development and poverty alleviation programs. Data collection process in the District Balong is still done manually so that the risk of error in determining the status of a family stage could happen. Information and analysis system of status stages of family welfare is designed to make web-based officers in the input data and determine the status of a prosperous family stages based on selected indicators of the sheet R/1/KS. Sample of data from Bulukidul village and sub-district village of Balong Ngraket 2014. Results of the system in the form of data reports the results of process steps and the results can be viewed in graphical form. Comparison chart to show the status of the highest percentage of poor welfare families stages. Instead lowest percentage shows the stages of a prosperous family able or rich.Â